Spatial environmental impact of immigration in Europe: Mediating roles of energy intensity and concentration - Ladan Ghodrati; Saeed Shouri; Masoud Shirazi (Energy Strategy Reviews)
With the growing trend in migration, studying the environmental effects of such international movements is becoming a controversial debate. Thus, the present study for the first time investigates the effects of immigration on environmental degradation in 19 European countries from 2000 to 2019. For this reason, a spatial panel model is employed to incorporate the geographical dependence of the studied variables. Specifically, two indices of ecological footprint per capita (EF) and Earth equivalent (EE) are used. Also, the stepwise regression model is employed to investigate the mediating effects of energy intensity and energy concentration on the environmental degradation. The results reveal a positive impact of immigration on environmental deterioration with greater vulnerability of the EE than the EF and highlights the significant spatial effects: environmental consequences of immigration extend beyond the borders and deteriorates the sustainability of neighboring countries. Mediating analysis reveals that energy concentration intensifies the environmental effects of migration via resource usage and energy consumption, while energy intensity mitigates EF and EE either through the negative correlation between EI and ECI or the composition and technique effects associated with cleaner activities in response to the higher knowledge and greater technological and economic progress. The findings highlight the cross-border cooperation in migration and energy policies. Thus, decision-makers should take practical steps to control the migration driven energy demand, encourage the use of green energy and diversify energy portfolio. Such approaches can accelerate the sustainable development with the reduction in environmental pressures.